A comparative analysis of authorized and unauthorized compound terms taken from the Library of Congress subject headings in information retrieval - Bernabe, Mary Jean Z.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This study is a comparative analysis of the authorized and unauthorized terms taken from the Library of Congress Subject Headings. It focused in which of the paired terms-authorized / LCSH or unauthorized/non-LCSH would give better recall and precision.
One hundred seventy-six (176) paired terms were drawn from the LCSH for this study. Paired terms consists of the authorized and unauthorized terms taken from the list. However, only 31 paired terms and 26 LCSH terms with hits were used in the study.
Documents retrieved were said to be relevant when its call numbers were exactly the same or within the brackets of the equivalent call numbers of each LCSH term. Recall on the other hand, was based on the value of the numerator, which is the number of relevant hits. This means that the recall value is not the absolute value for recall but only a comparative recall since it is assumed that both terms are identical in terms of the number of relevant documents in the database. Subsequently, paired sample sign test and one sample t test are used to analyze the data.
Thus, the analysis showed that the LCSH compound terms obtain higher precision and recall than the non-LCSH terms using the paired sample sign test and one sample t test at the .05 and .01 level of significance. Except for the case of one sample t test of a = .01 for precision where there is no significant difference in precision between the LCSH and non-LCSH terms.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information retrieval; Subject headings, Library of Congress